2004
DOI: 10.1007/s10350-004-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Repair of Obstetric Anal Sphincter Rupture: Medium-Term Outcome of the Overlap Technique

Abstract: The median-term outcome of primary overlap repair for obstetric sphincter rupture is good; however, larger, randomized studies with a longer follow-up are needed to evaluate the advantage of this technique over the end-to-end technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Based on the present and previous results, [32][33][34] we suggest that the overlap technique should be adopted as the method of choice for primary sphincter repair after obstetric tear and close cowork between obstetricians and colorectal surgeons is essential. Moreover, in patients with poor clinical outcome, EAUS is the best method to evaluate the anatomic result of sphincter reconstruction.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Based on the present and previous results, [32][33][34] we suggest that the overlap technique should be adopted as the method of choice for primary sphincter repair after obstetric tear and close cowork between obstetricians and colorectal surgeons is essential. Moreover, in patients with poor clinical outcome, EAUS is the best method to evaluate the anatomic result of sphincter reconstruction.…”
Section: Discussionmentioning
confidence: 71%
“…Three studies have shown good results from the primary overlap technique. [32][33][34] Conversely, two prospective studies comparing overlap and end-to-end techniques showed no difference in postoperative result. 38,39 These two studies had a follow-up time of only three to four months.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Generally speaking, obstetricians commonly use the former [52], while the latter is the predominant technique of colorectal surgeons [53]. Outcome studies show varying results for the two techniques [54][55][56].…”
Section: Sphincter Rupture and Repairmentioning
confidence: 99%
“…The incidence of anal incontinence is increased with anal sphincter laceration (ASL). Studies indicate that 23-60% of women diagnosed with a third-or fourth-degree obstetrical laceration reported anal incontinence after 1 year despite primary repair of their injury [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%